Insight into the Last Glacial Maximum climate and environments of the Baikal region. (14th June 2018) - Tarasov, Pavel E.; Ilyashuk, Boris P.; Leipe, Christian; Müller, Stefanie; Plessen, Birgit; Hoelzmann, Philipp; Kostrova, Svetlana S.; Bezrukova, Elena V.; Meyer, Hanno
Abstract : This study presents a multi‐proxy record from Lake Kotokel in the Baikal region at decadal‐to‐multidecadal resolution and provides a reconstruction of terrestrial and aquatic environments in the area during a 2000‐year interval of globally harsh climate often referred to as the Last Glacial Maximum (LGM). The studied lake is situated near the eastern shoreline of Lake Baikal, in a climatically sensitive zone that hosts boreal taiga and cold deciduous forests, cold steppe associations typical for northern Mongolia, and mountain tundra vegetation. The results provide a detailed picture of the period in focus, indicating (i) a driest phase ( c . 24.0–23.4 cal. ka BP) with low precipitation, high summer evaporation, and low lake levels, (ii) a transitional interval of unstable conditions ( c . 23.4–22.6 cal. ka BP), and (iii) a phase ( c . 22.6–22.0 cal. ka BP) of relatively high precipitation (and moisture availability) and relatively high lake levels. One hotly debated issue in late Quaternary research is regional summer thermal conditions during the LGM. Our chironomid‐based reconstruction suggests at least 3.5 °C higher than present summer temperatures between c . 22.6 and 22.0 cal. ka BP, which are well in line with warmer and wetter conditions in the North Atlantic region inferred from Greenland ice‐cores. Overall, it appears that environments in central Eurasia during the LGM were affected by much colder than present winter temperatures and higher than present summer temperatures, although the effects of temperature oscillations were strongly influenced by changes in humidity.